Reply to the Comment on: Marco Cirillo The Memory of the Heart. J. Cardiovasc. Dev. Dis. 2018, 5, 55 - Marco Cirillo (Journal of Cardiovascular Development and Disease, 2018)
I was disappointed by Anderson’s comment on my recent review, a comment that I think derives from a too quick reading of the article. [...]